Faktor-faktor yang Memengaruhi Perilaku Judi Online pada Remaja: Narrative Literature Review - Mayradevi, Ida Ayu Pringga; Tobing, David Hizkia (Jurnal Psikologi Perseptual, 2024)
Online gambling is the act of wagering money or valuable items to gain profits in which the amount is uncertain. Recently, online gambling has become prevalent among young people, and in this context, adolescents are prone to engaging in activities which can be detrimental to themselves and other people by committing acts of indecency like thievery and selling valuable items that can belong to others. Online gambling also has several negative impacts on the lives of adolescents, including a decline in academic performance, emotional instability, poor relationships with others, and gambling disorders. This research aims to examine the factors influencing online gambling behavior in adolescents. The study utilizes a literature review method with a narrative review type. The articles were accessed through sources such as Google Scholar, PubMed, Springer, and Science Direct, with publication years ranging from 2013 - 2023. Based on the literature review findings, five major categories were identified, including factors originating from the individual, family, social environment, socio-economic, and internet features. This literature review is expected to provide readers with comprehensive information on the factors that lead adolescents to engage in online gambling behavior. Additionally, it aims to serve as a foundation for developing interventions to address this issue. Judi online adalah tindakan mempertaruhkan uang atau barang berharga untuk mendapatkan keuntungan yang tidak pasti. Saat ini, judi online semakin marak terjadi di kalangan remaja, dan dalam hal ini, remaja rentan terlibat dalam aktivitas yang dapat merugikan diri sendiri dan orang lain, seperti mencuri dan menjual barang-barang berharga. Judi online juga memberikan dampak negatif terhadap kehidupan remaja, beberapa diantaranya adalah penurunan prestasi akademik, ketidakstabilan emosi, hubungan yang buruk dengan orang lain, dan gangguan perjudian. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi perilaku judi online pada remaja. Penelitian ini menggunakan metode literature review dengan tipe narrative review. Sumber pencarian artikel diakses melalui sumber pustaka Google Scholar, PubMed, Springer, dan Science Direct dengan tahun publikasi rentang 2013 – 2023. Berdasarkan hasil pengkajian literatur, diperoleh lima kategori utama, yaitu faktor yang berasal dari individu, keluarga, lingkungan sosial, sosial ekonomi, dan fitur internet. Literature review ini diharapkan dapat memberikan informasi yang komprehensif kepada pembaca mengenai faktor-faktor yang menyebabkan remaja melakukan dan mempertahankan perilaku judi online, serta dapat menjadi landasan dalam pengembangan intervensi untuk mengatasi situasi tersebut.